2014
DOI: 10.1002/smr.1665
|View full text |Cite
|
Sign up to set email alerts
|

A project management improvement program according to ISO/IEC 29110 and PMBOK®

Abstract: This paper describes the results obtained and the lessons learned from the implementation of the ISO/IEC 29110 standard in four small software development companies, clustered in a joint process improvement program. The main results of this initiative have been, on the one hand, the definition of a standardized set of processes and procedures and, on the other, the development of a Process Asset Library to support project management good practices within the participant organizations. The PMBOK® Guide was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 4 publications
0
23
0
1
Order By: Relevance
“…Literature reports contributions related to the ISO/IEC 29110 25 in several industrial contexts. [26][27][28][29][30] Basically, these contributions are related to its adoption, 31,32 but in general their contributions are wide. 33 In fact, this kind of organisations is facing several hurdles 34 including project management and software implementation perspectives.…”
Section: Very Small Entities and System Life-cycle Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reports contributions related to the ISO/IEC 29110 25 in several industrial contexts. [26][27][28][29][30] Basically, these contributions are related to its adoption, 31,32 but in general their contributions are wide. 33 In fact, this kind of organisations is facing several hurdles 34 including project management and software implementation perspectives.…”
Section: Very Small Entities and System Life-cycle Processesmentioning
confidence: 99%
“…Literature reports contributions related to the ISO/IEC 29110 in several industrial contexts . Basically, these contributions are related to its adoption, but in general their contributions are wide .…”
Section: Introductionmentioning
confidence: 99%
“…Software Quality Journal published a Special Issue on the topic, and papers contained there include aspects like risk in software testing and practices actually used by companies, naming just 2 of the most important papers published in the special section. However, there is a long tail of papers published in previous editorial efforts on SPI and SMEs by members of the community, eg, the studies of Mesquida and Mas, and Larrucea et al…”
Section: About the Special Issuementioning
confidence: 99%
“…Apart from the traditional topic of tool development, 2 main pillars are supporting the paper in terms of research topics: project management and service portfolio management. Regarding the first topic, several works have tackled the subject in recent papers dealing with project management in small settings, compliance with PMBOK or process reference models and regarding service portfolio Management. Papers dealing with the topic include ITIL implementation sequence suggestions or the TIPA framework …”
Section: About the Special Issuementioning
confidence: 99%
“…Several industrial experiences have been reported applying the ISO/IEC 29110 . Its adoption is controversial, and researchers have provided contributions from several ISO/IEC29110 perspectives .…”
Section: Introductionmentioning
confidence: 99%